2020
DOI: 10.1002/cctc.201902053
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Quantification of Edge Sites of WS2/Al2O3 Catalysts Coupling IR/CO Spectroscopy and DFT Calculations

Abstract: IR spectroscopy of CO adsorption (IR/CO) and Density Functional Theory (DFT) calculations on sulfide W/Al2O3 catalyst were investigated for an insight into the sulfide edge sites. Parallel between experimental and theoretical results allow to assign the ν(CO) bands at 2121 and 2066 cm−1 to CO adsorption on M‐ and S‐edge sites of WS2 phase, respectively. Through a careful analysis of CO spectra on well‐selected W catalysts, the molar attenuation coefficients for CO adsorbed on the two exposed edges could be det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…From these IR spectra, it is observed that the addition of Ni to W brings three new bands at 2127, 2093 and 2079 cm −1 . These wavenumbers are very close to those reported by Duchet et al [31], Zuo et al [15], Travert et al [33] and more recently by Zavala-Sanchez [28,29]. These authors proposed that these three bands characterize interaction between Ni and W but with different environments.…”
Section: Ir Spectroscopy Of Adsorbed Co Probesupporting
confidence: 89%
See 2 more Smart Citations
“…From these IR spectra, it is observed that the addition of Ni to W brings three new bands at 2127, 2093 and 2079 cm −1 . These wavenumbers are very close to those reported by Duchet et al [31], Zuo et al [15], Travert et al [33] and more recently by Zavala-Sanchez [28,29]. These authors proposed that these three bands characterize interaction between Ni and W but with different environments.…”
Section: Ir Spectroscopy Of Adsorbed Co Probesupporting
confidence: 89%
“…Infrared spectroscopy of adsorbed CO provides interesting information for investigation of the surface species of sulfide catalysts like the NiW ones. In particular, IR signal of CO (IR/CO) allows discriminating unpromoted W phase from NiWS one [15,28,29]. Figures 5,6 and 7 show the IR spectra of CO adsorbed on sulfided W, NiW and NiW(4.0), respectively.…”
Section: Ir Spectroscopy Of Adsorbed Co Probementioning
confidence: 99%
See 1 more Smart Citation
“…In that sense, in-situ IR spectroscopy is a powerful technique for investigating the interaction modes of adsorbates on zeolite active sites. [39,40] The combination of experiments and predictive calculations for IR spectra can be critical for the allocation of the spectra related to the adsorption modes of the different adsorbate/adsorbent systems. [39][40][41][42] In the present work, in-situ IR spectroscopy experiments have been combined with periodic DFT in order to assign the vibrational frequencies of the different adsorption modes of phenol and toluene over proton and sodium exchanged zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…[39,40] The combination of experiments and predictive calculations for IR spectra can be critical for the allocation of the spectra related to the adsorption modes of the different adsorbate/adsorbent systems. [39][40][41][42] In the present work, in-situ IR spectroscopy experiments have been combined with periodic DFT in order to assign the vibrational frequencies of the different adsorption modes of phenol and toluene over proton and sodium exchanged zeolites. The interaction energy of the most stable adsorbed configuration of phenol and toluene have been compared for the two zeolites with the purpose to select the most suitable cation-type for achieving the selective removal of phenol from synthetic biofuel feed (isooctane + 1 wt.% phenol + 1 wt.% n-nonane + 40 wt.% toluene).…”
Section: Introductionmentioning
confidence: 99%